Design, synthesis and antitumor activity of Novel Sorafenib derivatives bearing pyrazole scaffold. Issue 20 (15th October 2017) - Wang, Min; Xu, Shan; Lei, Huajun; Wang, Caolin; Xiao, Zhen; Jia, Shuang; Zhi, Jia; Zheng, Pengwu; Zhu, Wufu
Graphical abstract: Highlights: Four series of Sorafenib derivatives bearing pyrazole scaffold (8a –m, 9a –c, 10a –e and11a ) were synthesized and characterized. Most of the synthesized compounds showed moderate to significant antitumor activity. Docking study was investigated to explore the binding modes of compounds with VEGFR and c-Met. Abstract: Four series of Sorafenib derivatives bearing pyrazole scaffold (8a –m, 9a –c, 10a –e and11a ) were synthesized and characterized by NMR and MS. All of the target compounds were evaluated for the cytotoxicity against A549, HepG2, MCF-7, and PC-3 cancer cell lines and some selected compounds were further evaluated for the activity against VEGFR-2/KDR, BRAF, CRAF, c-Met, EGFR and Flt-3 kinases. Compounds 8b and 8i were more active than that of compounds 8h, 9a, especially the IC50 value of compounds 8b on VEGFR-2 kinase was 0.56 μM. And compound 8b exhibited moderate to good activity toward c-Met and showed moderate to no activity against CRAF, c-Met, EGFR, Flt-3 kinases. Eleven of the target compounds exhibited moderate to good antitumor activities. The most promising compound8b showed strong antitumor activities against A549, HepG2 and MCF-7 cell lines with IC50 values of 2.84 ± 0.78 μM, 1.85 ± 0.03 μM and 1.96 ± 0.28 μM, which were equivalent to Sorafenib (2.92 ± 0.68 μM, 3.44 ± 0.50 μM and 3.18 ± 0.18 μM). Structure–activity relationships (SARs) and docking studies indicated that the pyrazole scaffolds exerted key effect on antitumor activities of target compounds. Substitutions of aryl group at C-3 positions had a significant impact on the antitumor activities, and 3-Br substitution produced the best potency.